ART BRUT : le livre des livres. - Garcia Munoz, Graciela; Berst, Élisabeth; Berst, Christian (Milan : 5 Continents Editions, 2022)
Drager, Henry ; Wölfli, Adolf ; Corbaz, Aloïse ; Antinéa ; Aiken, Beverly Gayleen ; Castle, James ; Blauvelt, Pearl ; Histe, Henri ; Mikolajewski, Peter ; Walla, August ; Heinrichshofen, Rudolf ; Klose, August Johan ; Voll, Oskar ; Deeds Jr, James Edward ; Anonyme ; von Schwartzenberg, Alexander ; Steffen, Charles ; McKesson, Malcolm ; Benetto, Éric ; Iselstöger, Aurel ; ...
For the first time brought together in a single publication, L’Art Brut. The book of books, allows you to discover more than sixty works by visionary artists, mystical geniuses and literary madmen who make up the panorama of this artistic current. Art Brut – adored by great artists as well as by neophytes – has now reached its rightful rank, entering the major museum collections and international exhibitions. The fact that these productions do not seem to be explicitly dedicated to anyone other than their authors does not, however, deprive them of their charm and importance: it is precisely in this way that Brut artists take the risk of their own production and self-referentiality towards their public, presenting the notebooks and books of which they are the authors. These works, sometimes conceived inside psychiatric hospitals, are the result of the isolation in which they find their inspiration, in an intimate dialogue with their secrets and their deepest selves. The writing becomes drawing in a graphic and emotional continuum, where esoteric tracts, history books, autobiographical soliloquies and sketchbooks are mixed together. Discovering this volume and the stories it contains brings the reader closer and reveals, page after page, the obsessions of the artists, their passions, to make us discover a deep humanity. (provided by publisher)
boek